BLOCK OF PARAMETRIC COGNITIVE MODELS FOR SYSTEM ANALYSIS OF INFORMATIONAL EXCHANGE EFFICIENCY IN AN ADAPTIVE AUTOMATED TRAINING ENVIRONMENT - A. N. Vetrov (Вестник Дагестанского государственного технического университета: Технические науки, 2017)
.